The Role of Lecturers’ Facial Expressions in Emotional Interactions with EFL Learners - G, Hasriani; Dollah, Syarifuddin; Risan, Rahmad; Muhayyang, Maemuna; Sakkir, Geminastiti (Pascasarjana Universitas Negeri Makassar, 2025)
Lecturers’ facial expressions are a primary non-verbal cue, often conveying encouragement, approval, or even subtle disapproval, which can significantly affect learners’ comfort, confidence, and willingness to participate in the classroom interaction. This study investigated the role of lecturers’ facial expression in emotional interactions with EFL learners. The researcher focused on investigating the influence of lecturers’ on EFL learners’ emotional response as well as learners’ motivation and engagement, and learners’ interpretation and response to the lecturers’ facial expression. The data collected through questionnaire, interview, and observation. The researcher then analyzed the data qualitatively. The findings from this research support the notion that lecturers' facial expressions significantly influence learners’ emotional responses, motivation, engagement, and confidence in the classroom. Positive facial expressions, such as smiles and enthusiastic expressions, can create a supportive and comfortable learning environment, motivating learners to participate actively and enhancing their overall learning experience. Furthermore, cultural differences must be considered, as learners may interpret facial expressions in diverse ways, highlighting the need for lecturers to be mindful of their non-verbal cues.